2005
DOI: 10.1139/f05-103
|View full text |Cite
|
Sign up to set email alerts
|

Methyl mercury concentrations in macroinvertebrates and fish from burned and undisturbed lakes on the Boreal Plain

Abstract: Methyl mercury (MeHg) concentrations in macroinvertebrates and fish were compared among five lakes in burned catchments and five reference lakes on the western Canadian Boreal Plain to determine the influence of forest fire on MeHg bioaccumulation. Two years after fire, MeHg concentrations in five of six aquatic taxa were similar in burned and reference lakes. Among a larger set of 12 lakes, MeHg concentrations in biota were negatively correlated with lake water pH, trophic status, and hardness, reflecting a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…We hypothesize that fire characteristics (i.e., fire severity, proportion of catchment burned, and timing and intensity of runoff) influence limiting nutrient and contaminant release from burned catchments, altering the relative importance of the two Hg accumulation mechanisms. This hypothesis provides an explanation for the differing results from studies conducted in severely and/or fully burned catchments (19,43,44). The postfire changes in Hg cycling observed in this study are likely not unique to Moab Lake.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…We hypothesize that fire characteristics (i.e., fire severity, proportion of catchment burned, and timing and intensity of runoff) influence limiting nutrient and contaminant release from burned catchments, altering the relative importance of the two Hg accumulation mechanisms. This hypothesis provides an explanation for the differing results from studies conducted in severely and/or fully burned catchments (19,43,44). The postfire changes in Hg cycling observed in this study are likely not unique to Moab Lake.…”
Section: Resultsmentioning
confidence: 59%
“…Fire-mobilized nutrients (usually N and sometimes P) (16) can enhance lake productivity (17). Forest fire also has been shown to cause small increases in ␦ 15 N of aquatic organisms (17)(18)(19), which some attributed to increased inputs of inorganic nitrogen from the catchment (18,19), not food web alterations. Few have studied the effects of forest fire on the biogeochemical cycling of Hg.…”
mentioning
confidence: 99%
“…In many circumstances this is likely the case, particularly in areas where inorganic Hg deposition is low and bioaccumulation is driven by MeHg production and availability. Allen et al (2005) found that biomagnification was inversely correlated with chlorophyll a concentrations in a series of lakes, suggesting that biodilution regulated transfer of MeHg to higher trophic levels. Moreover, MeHg concentrations in biota were negatively correlated with pH, indicating that entry into the food web was controlled by water chemistry.…”
Section: Discussionmentioning
confidence: 96%
“…In lakes, burns have been shown to increase productivity due to nutrient enrichment (Garcia and Carignan 2005). Increases in productivity have led to changes in growth rates of macro-invertebrates, and in turn shifted diet preferences of fishes (Kelly et al 2006;Allen et al 2005). Dietary alterations can lead to enhanced growth of Northern Pike and other fishes, and longer food chains can occur in post-fire lakes as a result of increased productivity restructuring food webs and enhancing the trophic position of piscivores (Kelly et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature on the effect of forest fires on lacustrine environments have focused on contaminants transfer (Allen et al 2005;Garcia and Carignan 2005;Kelly et al 2006) and fish-community interactions (St-Onge and Magnan 2000; Tonn et al 2003;. No specific information exists on the effects of forest fire on spawning and rearing Northern Pike, or their habitats in the Northwest Territories (NWT).…”
Section: Effects Of Forest Fire On Young-of-the-year Northern Pike Ementioning
confidence: 99%